(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article considers the project method as one of the types of pedagogical technology. A sample of a mini-project is given to activate the speech activity of students. The goals and objectives of the mini-project for upper school students with Uzbek language of instruction in general education schools have been identified.